Administration of Lactobacillus fermentum CRL1446 increases intestinal feruloyl esterase activity in mice - Abeijon Mukdsi, Maria Claudia (2012)
Aims: To evaluate the effect of oral administration of Lactobacillus fermentum CRL1446 on the intestinal feruloyl esterase (FE) activity and oxidative status of mice. Methods and Results: Adult Swiss albino mice received Lact. fermentum CRL1446 at the doses 107 and 109 cells per day per mouse for 2, 5, 7 and 10 days. Intestinal FE activity, intestinal microbiota counts, plasmatic thiobarbituric acid-reactive substances (TBARS) percentage and glutathione reductase (GR) activity were determined. Mice that received Lact. fermentum CRL1446 at the dose 107 cells per day for 7 days showed a twofold increase in total intestinal FE activity, compared to the nontreated group. In large intestine content, FE activity increased up to 6Æ4 times. No major quantitative changes in colonic microbiota were observed in treated animals. Administration of this strain produced an approx. 30–40% decrease in the basal levels of plasmatic TBARS and an approx. twofold increase in GR activity from day 5 of feeding with both doses. Conclusions: Oral administration of Lact. fermentum CRL1446 to mice increases total intestinal FE activity, decreases the basal percentage of plasmatic lipoperoxides and increases GR activity. Significance and Impact of the Study: Lactobacillus fermentum CRL1446 could be orally administered as a dietary supplement or functional food for increasing the intestinal FE activity to enhance the bioavailability of ferulic acid, thus improving oxidative status.